Disseminated Tuberculosis in Breastfeeding Mother: A Case Report - Dewi Oktavia Djasmi; Roza Kurniati; Fauzar (HM Publisher, 2023)
Background: Disseminated tuberculosis is defined as the involvement of two or more extrapulmonary organs due to Mycobacterium tuberculosis infection, which spreads hematogenously. Disseminated tuberculosis is a life-threatening condition, especially if diagnosis and treatment are delayed. This study aimed to describe disseminated tuberculosis in a breastfeeding mother. Case presentation: A 21-year-old woman was admitted to Dr. M. Djamil General Hospital with chief complaints of shortness of breath. The symptoms were accompanied by chronic cough, fever, night sweats, and weight loss. From the physical examination, there was a decrease in left lung breath sounds as high as right intercostal V. On the gene expert results, the PCR was positive for Mycobacterium tuberculosis. Chest X-ray shows a miliary pattern and left pleural effusion. Pleural fluid analysis reveals the presence of exudate. Patients were treated with anti-tuberculosis drugs, namely Isoniazid, rifampicin, pyrazinamide, and ethambutol, with pyridoxine. Anti-tuberculosis drug therapy in the intensive phase is given for 2 months and is continued for 6-9 months for the continuation phase, depending on the patient's clinical condition. Breastfeeding was still continued in this case. The patient's baby is advised to be evaluated for active tuberculosis. Conclusion: There are no contraindications for giving anti-TB drugs to breastfeeding mothers unless the mother has mammary TB or drug-resistant TB. In children under 5 years who have close contact with active tuberculosis patients and, after being evaluated, do not have active tuberculosis, the child is treated as suspected latent TB infection with Isoniazid for at least 6 months and accompanied by pyridoxine administration.